Strength quality of tilapia and salmon skins submitted to tanning process with vegetable tannin (Research, Society and Development, 2021)
With the increase in aquaculture production, the amount of waste generated, as well as the skin of fish, also grows. The objective of this work was to carry out physical-mechanical analyzes of Nile tilapia (Oreochromis niloticus) and Salmon (Salmo salar) leathers submitted to tanning with vegetable tannins. Longitudinal specimens were removed to determine the tensile strength, elongation and progressive tearing of the leathers. Salmon leathers showed resistance parameters similar or superior to tilapia leathers. Salmon leather showed 96% elongation, at a maximum strength of 161.75N, while tilapia leather 114.75% and 127.00N, respectively for these same parameters. The applied force was 53.62N to generate a tear of 53.60N / mm, for salmon leathers, whereas tilapia leathers showed a tear of 40.56N / mm submitted to a force of 36.75N. Salmon leathers presented resistance quality similar or superior to tilapia leathers depending on the evaluated parameter.